Confronting Colonial Objects Histories, Legalities, and Access to Culture - Stahn, Carsten (Cultural Heritage Law and Policy, 2023)
In 1978, UNESCO Secretary General Amadou-Mahtar M'Bow compared cultural colonial objects to 'witnesses to history'. Their treatment is one of the most debated questions of our time. Calls for a novel international cultural order go back to decolonization. However, for decades, the issue has been treated as a matter of comity or been reduced to a Shakespearean dilemma: to return or not to return. This book seeks to go beyond these classic dichotomies. It argues that contemporary practices are at a tipping point. It shows that cultural takings were material to the colonial project throughout different periods (early takings, birth of modern nation state, nineteenth-century scramble for objects) and went far beyond looting. It relies on micro histories and object biographies to trace recurring justifications and contestations of takings and returns, and the complicity of anthropology, racial science, and professional networks in colonial collecting. It demonstrates the dual role of law and cultural heritage regulation in enabling colonial injustices, and mobilizing resistance thereto. It challenges the argument that takings were acceptable according to the standards of the time. Drawing on the interplay between justice, ethics, and human rights, it develops a theory of entanglement to rethink contemporary approaches. It shows that future engagement requires a reinvention of knowledge systems and relations towards objects, including new forms of consent, provenance research, partnership and a rethinking of the role of museums themselves. It proposes principles of relational cultural justice to confront ongoing historic, legal, and economic entanglements and enable normative transformation.